2007
DOI: 10.1103/physreve.76.041914
|View full text |Cite
|
Sign up to set email alerts
|

Inverted and mirror repeats in model nucleotide sequences

Abstract: We analytically and numerically study the probabilistic properties of inverted and mirror repeats in model sequences of nucleic acids. We consider both perfect and nonperfect repeats, i.e., repeats with mismatches and gaps. The considered sequence models are independent identically distributed (i.i.d.) sequences, Markov processes and long-range sequences. We show that the number of repeats in correlated sequences is significantly larger than in i.i.d. sequences and that this discrepancy increases exponentially… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The S. cerevisiae genome is significantly enriched in perfect inverted repeats relative to random. Figure 6 plots in semilog coordinates the number of perfect IRs as a function of copy length for the S. cerevisiae , R, and RA genomes, together with expected numbers calculated using a theoretical method presented elsewhere (Lillo and Spano 2007 ). At every copy length the perfect IR number is statistically significantly higher in the S. cerevisiae genome than in either the R or the RA genomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The S. cerevisiae genome is significantly enriched in perfect inverted repeats relative to random. Figure 6 plots in semilog coordinates the number of perfect IRs as a function of copy length for the S. cerevisiae , R, and RA genomes, together with expected numbers calculated using a theoretical method presented elsewhere (Lillo and Spano 2007 ). At every copy length the perfect IR number is statistically significantly higher in the S. cerevisiae genome than in either the R or the RA genomes.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors (Lillo et al 2002 ; Lillo and Spano 2007 ) have presented formulas to compute the expected number of perfect IRs as a function of copy length in a sequence. We verified these formulas and also used them for the same purpose.…”
Section: Methodsmentioning
confidence: 99%
“…They play an important role in the regulation of transcription and translation (Varshney et al, 2020). Even in bacteria, inverted repeats and their associated hairpin structure are frequently found as a part of the independent transcription terminal (Brazda et al, 2020;Lillo and Spanò, 2007). Direct repeats are the sequences that are repeated multiple times on the same strand of DNA in the same orientation (Mirkin, 2001).…”
mentioning
confidence: 99%
“…Hairpin structures have been investigated in quite different organims with a variety of methods. Examples of these studies can be found in Ref.s [5,6,7,8,9,10,11,12,13,14] In this paper we detect candidate RNA secondary structures which are characterized by a minimal value of the free energy of the strucure in the folded state. In a first investigation the free energy is estimated by using Mfold, which is a reference software for the estimation of the free energy of RNA secondary structures.…”
mentioning
confidence: 99%